Identification Tests of Modern Vehicles’ Electromagnetic Environment as Part of the Assessment of Their Functional Safety - Daniel Sterniczuk; Weronika Zaklika; Maciej Kozłowski (Sensors)
Are the regulations relating to electromagnetic compatibility (EMC) sufficient to ensure the safety of all autonomy systems? EMC is one of the critical factors influencing the proper functioning of a vehicle and its safety. However, the safety of autonomous vehicles from the perspective of EMC has not been comprehensively researched to date. The purpose of this article is to evaluate whether the currently imposed requirements are adequate. To assess research methods and requirements, it is necessary to determine the electromagnetic environment of vehicles. For this purpose, identification tests of the vehicle’s operating environment were conducted. The article presents the results of research on both the internal and external electromagnetic environments of vehicles. These studies were carried out using normative methods. Despite the significant importance of EMC and the existence of defined normative requirements, the results of the conducted research indicate that some devices available on the market, including those unrelated to vehicle autonomy, fail to meet these standards. Consequently, devices responsible for vehicle safety must be resistant to such electromagnetic exposures. In extreme cases, the malfunction of a single vehicle component due to inadequate electromagnetic compatibility could lead to the disruption of vehicle functions or driver disorientation. Such occurrences pose a direct threat to road traffic safety and the well-being of passengers.